The Effectiveness of Mindfulness-Based Cognitive Therapy on Rumination and Cognitive Bias in Individuals Referred to Counseling Centers - Golkarian, Bita; BozorgnezhadDivkolae, Mehdi; Ghanbari, Maedeh; Samkhaniani, Eshagh; Soleimani Arzefuni, Somayeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to determine the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) on reducing rumination and cognitive bias among individuals referred to counseling centers. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group framework. The statistical population consisted of individuals referred to the Arsam Psychological Services and Counseling Center in Tonekabon, Iran, during 2025. A total of 30 participants were selected through convenience sampling and randomly assigned to either an experimental group (n = 15) or a control group (n = 15). Data were collected using the Rumination Response Scale (RRS) and the Cognitive Bias Questionnaire. Participants in the experimental group received eight weekly 90-minute sessions of Mindfulness-Based Cognitive Therapy, while the control group received no psychological intervention. Data were analyzed using repeated-measures analysis of variance after verifying assumptions of normality through the Shapiro–Wilk test. Findings: Inferential analyses demonstrated significant effects of time on rumination scores (F = 78.427, p < .001, η² = .653) and a significant time × group interaction (F = 16.354, p < .001, η² = .521), indicating that participants who received MBCT experienced substantial reductions in rumination compared with the control group. Similarly, cognitive bias scores showed a significant effect of time (F = 105.553, p < .001, η² = .785) and a significant time × group interaction (F = 31.186, p < .001, η² = .548). These findings suggest that the intervention produced meaningful improvements in both outcome variables, whereas no comparable changes were observed in the control group. Conclusion: The findings indicate that Mindfulness-Based Cognitive Therapy is an effective intervention for reducing rumination and cognitive bias among individuals seeking counseling services. By enhancing present-moment awareness, nonjudgmental attention, and cognitive flexibility, MBCT helps individuals disengage from maladaptive thought patterns and biased information processing.